Primary school children's knowledge of, and attitudes towards, healthy computer use - Tran, Thuy; Ciccarelli, Marina (IOS Press, 2012)
Background: Australian children as young as five years are using computers in the home and school environments with increased frequency and longer duration as they age. Consequently, they may be exposed to risk factors for the development of physical health problems described in studies of adult computer users. To date schools have focused on providing children with the latest computer technologies; with far less attention given to appropriate workstations, ergonomics education and incorporating safe computing practices. By better understanding children’s attitudes and knowledge, a directional approach to the development of an ergonomics education program may be established using a health promotion framework to encourage healthy computing behaviors. Objective: The purpose of this study was to identify children’s knowledge of, and attitudes towards healthy computing. Method: A cross-sectional inferential study of 537 Australian school children (aged 9 to 11 years) from Catholic Education Schools across Western Australia was conducted. Multiple logistic regression analyses identified that children’s beliefs and attitudes about the negative health effects of computers were found to be most associated with unhealthy computing behaviors. Results: Children lacked sufficient knowledge about the importance of postural and task variation, but had sufficient knowledge about adjusting workstation furniture specific to healthy computer use.